The Neurophysiological Bases of Emotion: An fMRI Study of the Affective Circumplex Using Emotion-Denoting Words
Objective We aimed to study the neural processing of emotion-denoting words based on a circumplex model of affect, which posits that all emotions can be described as a linear combination of two neurophysiological dimensions, valence and arousal. Based on the circumplex model, we predicted a linear relationship between neural activity and incremental changes in these two affective dimensions.

(untitled) - Posner, Jonathan; Russell, James A.; Gerber, Andrew; Gorman, Daniel; Colibazzi, Tiziano; Yu, Shan; Wang, Zhishun; Kangarlu, Alayar; Zhu, Hongtu; Peterson, Bradley S. (Human brain mapping, 2009)